SISTEM PENDUKUNG KEPUTUSAN USULAN KENAIKAN PANGKAT DAN GOLONGAN DENGAN MENGGUNAKAN METODE GAP PADA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI NUSA TENGGARA TIMUR - Yohanis Malelak (STMIK KHARISMA Makassar, 2016)
Proposed Decision Support Systems Group promotion and using the GAP Method of Culture And Tourism In East Nusa Tenggara Province is an artificial intelligence system that is built to determine prospective civil servants promoted to be proposed and studied them to the authorities. This determination is made by processing the data and their prospective employees work performance during the active period along with the criteria or rules of employee promotion requirements. The advantage of this is built DSS is able to provide fast and precise decisions and has a database that can accommodate mampuh data in large sizes and quantities so that the data storage medium used is more accurate. GAP or profile matching method is a method for comparing the criteria against which the reference criteria in order to find the value of each existing profile. From the discussion, it can be concluded that the presence of